The Influence of Store Atmosphere and Service Quality on Consumer Satisfaction at Simetri Coffee Roaster, Bekasi City, West Java - Jasmani Jasmani; Triyadi Triyadi; Ahmad Lutfi; Jaja Suteja; Denok Sunarsi (Sharia Business Management Department of STEBIS Bina Mandiri, 2026)
This study aims to determine the effect of store atmosphere and service quality on customer satisfaction at Simetri Coffee Roaster in Bekasi City, West Java. The method used was explanatory research, with statistical analysis techniques including regression, correlation, determination, and hypothesis testing. The results of this study indicate that store atmosphere significantly influences customer satisfaction, contributing 45.2%, with a calculated t-value > t-table (8.989 > 1.984). Service quality significantly influences customer satisfaction, contributing 42.4%, with a calculated t-value > t-table (8,500 > 1,984). Store atmosphere and service quality simultaneously significantly influence customer satisfaction, with a regression equation of Y = 5.849 + 0.450X1 + 0.409X2, contributing 60.6%, with a calculated F-value > F-table (74.727 > 2.700).